2013
DOI: 10.1186/1471-2229-13-150
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of WRKY45-regulated genes that mediate benzothiadiazole-induced defense responses in rice

Abstract: BackgroundThe rice transcription factor WRKY45 plays a crucial role in salicylic acid (SA)/benzothiadiazole (BTH)-induced disease resistance. Its knockdown severely reduces BTH-induced resistance to the fungal pathogen Magnaporthe oryzae and the bacterial pathogen Xanthomonas oryzae pv. oryzae (Xoo). Conversely, overexpression of WRKY45 induces extremely strong resistance to both of these pathogens. To elucidate the molecular basis of WRKY45-dependent disease resistance, we analyzed WRKY45-regulated gene expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(96 citation statements)
references
References 56 publications
3
88
1
Order By: Relevance
“…5C; Supplemental Fig. S6B), which is consistent with a previous report on rice infected with Magnaporthe oryzae (Nakayama et al, 2013). Remarkably, WRKY45-kd plants exhibited disease susceptibility, characterized by a large number of S. hermonthica seedlings that attached and developed: the number of S. hermonthica seedlings attaching to roots of WRKY45-kd plants was almost 3-fold higher compared with wild-type cv Nipponbare (Fig.…”
Section: Ja Potently Induces Resistance Against S Hermonthica Parasisupporting
confidence: 91%
See 3 more Smart Citations
“…5C; Supplemental Fig. S6B), which is consistent with a previous report on rice infected with Magnaporthe oryzae (Nakayama et al, 2013). Remarkably, WRKY45-kd plants exhibited disease susceptibility, characterized by a large number of S. hermonthica seedlings that attached and developed: the number of S. hermonthica seedlings attaching to roots of WRKY45-kd plants was almost 3-fold higher compared with wild-type cv Nipponbare (Fig.…”
Section: Ja Potently Induces Resistance Against S Hermonthica Parasisupporting
confidence: 91%
“…However, BTH application can induce resistance even in WRKY45-kd plants, suggesting that downstream components in the WRKY45-independent SA/BTH pathway are also able to contribute to resistance against S. hermonthica in rice. Such a pathway is likely to be the NH1/OsNPR1 pathway, as shown previously (Shimono et al, 2007;Nakayama et al, 2013). The involvement of JA in the NH1/OsNPR1 pathway is unlikely, because foliar BTH application onto the hebiba mutants is able to induce resistance (Supplemental Fig.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…However, Pb1 encodes an R protein-like CC-NB-LRR protein with atypical NB domain . Our recent studies showed that Pb1 specifically interacts with rice WRKY45 (Shimono et al 2007(Shimono et al , 2012Takatsuji et al 2010;Nakayama et al 2013;Akagi et al 2014;Takatsuji 2014), a TF that plays a major role in the salicylic acid signaling pathway, and that the blast resistance due to Pb1 is dependent on WRKY45 . Rice WRKY45 is regulated by ubiquitin-proteasome degradation in the nuclei to suppress untimely defense activation in the absence of pathogen infection .…”
Section: Introductionmentioning
confidence: 99%